Uso público e as atividades de visitação noturna nos parques nacionais do Brasil - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
Tourism in natural areas has been growing and diversifying in recent years. Seeking to attract visitors, new visitation proposals are offered. This research aims to diagnose night activities for public use in the National Parks of Brazil, aiming at proposing national guidelines for night visitation in protected areas of full protection. For this purpose it will be used as a parameter for the research the identification of night activities in the Brazilian national parks, the existing practices, operational aspects, visitor control, norms and rules of visitation. Although the aspects of the use of night space-time are more present in urban offerings, it is important to present a conceptual review about this theme and to identify the proposals, as well as to verify the potentialities and vulnerabilities in the public use of these spaces, in this type of tourist activity. The night visitation is developed in some protected areas in order to offer an innovative proposal for visitors, however, research is needed to verify this activity, in order to offer visitor safety, conservation of the area and quality management by its visitors. organizers so that they can consolidate themselves as new alternatives in ecotourism. The research used an online questionnaire sent to Brazilian national parks, analysis of management plans, bibliographic research and information analysis with their managers. This research identified different practices in natural areas at night, which were divided into three main categories: overnight activities and associated activities, night trails and walks, and night diving. It has been identified that parks that carry out these proposals have established rules and regulations for their actions, and also seek to limit or control the number of people who practice them daily. There are still no guidelines to guide the practice of night visitation in natural areas, with the results obtained the elaboration of proposals for both managers and visitors, which were based on the guidelines already formulated by the Ministry of Environment for other visitation activities. , in the proposals already implemented and presented in the management plans, in the examples of activities developed in other countries and in the bibliographic reading that guided the studies of this research, such as night management and tourism in natural areas.
Keywords: Uso público; Visitação noturna; Ecoturismo; Diretrizes; Parques nacionais; Public use; Night visit; Ecotourism; Guidelines; National parks; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA